Prevotella abundance and salivary amylase gene copy number predict fat loss in response to wholegrain diets - Christensen, Lars; Hjorth, Mads F.; Krych, Lukasz; Licht, Tine Rask; Lauritzen, Lotte; Magkos, Faidon; Roager, Henrik M. (Frontiers in Nutrition, 2022)
Background: Salivary amylase (AMY1) gene copy number (CN) and Prevotella abundance in the gut are involved in carbohydrate digestion in the upper and lower gastrointestinal tract, respectively; and have been suggested as prognostic biomarkers for weight loss among overweight individuals consuming diets rich in fiber and wholegrains. Objective: We hypothesized that Prevotella abundance would be linked to greater loss of body fat after wholegrain consumption among individuals with low AMY1 CN, but not in those with high AMY1 CN. Methods: We reanalyzed data from two independent randomized ad-libitum wholegrain interventions (fiber intake 33 g/d for 6-8 weeks), to investigate the relationship between baseline Prevotella abundance and body fat loss among healthy, overweight participants stratified into two groups by median AMY1 CN. Individuals with no detected Prevotella spp. were excluded from the main analysis. Results: In both studies, individuals with low AMY1 CN exhibited a positive correlation between baseline Prevotella abundance and fat loss after consuming the wholegrain diet (r > 0.5, P < 0.05), but no correlation among participants with high AMY1 CN (P ≥ 0.6). Following consumption of the refined wheat control diets, there were no associations between baseline Prevotella abundance and changes in body fat in any of the AMY1 groups. Conclusion: These results suggest that Prevotella abundance together with AMY1 CN can help predict fat loss in response to ad-libitum wholegrain diets, highlighting the potential of these biomarkers in personalized obesity management.